Observational assessment of the hygienic conditions of three fairs in the municipality of Manaus, AM, Brazil - L. E. S. Lima; M. A. Oliveira; I. N. B. Bussons; M. F. S. Gomes; A. T. Oliveira; M. R. F. M. Bussons (Boletim de Indústria Animal)
The consumer fishing operation can be engaged in fishing problems in consumer health, so the present work as structural conditions and manipulation of the municipal fair of Manaus. Observations were made at three Centro, Santo Antônio and Betânia district fairs. Note that the hygienic and sanitary conditions of the workers are precarious; in one of the fairs, it was possible to verify the protective equipment such as gloves, caps, the presence of animals near the window where the fish is exposed for sale, styrofoam boxes used for the storage in an inappropriate state, dirty and the company of parcels with fish on the floor without any secondary packaging for protection. Therefore, it is concluded that it is necessary to train users on the dangers that can affect the lack of adequate handling of the consumer's health, which may interfere directly with the local fishing sector.